The Temporally-Integrated Causality Landscape: Reconciling Neuroscientific Theories With the Phenomenology of Consciousness - Winters, Jesse J. (Frontiers in Human Neuroscience, 2021)
In recent years, there has been a proliferation of neuroscientific theories of consciousness. These include theories which explicitly point to EM fields, notably Operational Architectonics and General Resonance Theory. Human consciousness is a unified composition of contents. These contents are specific and meaningful, and they exist from a subjective point-of-view. Human conscious experience is temporally continuous, limited in content, and coherent. Based upon those phenomenal observations, pre-existing theories of consciousness, and a large body of experimental evidence, I derived the Temporally-Integrated Causality Landscape (TICL). In brief the TICL proposes that the neural correlate of consciousness is a structure of temporally-integrated causality occurring over a large portion of the thalamocortical system. This structure is composed of a large, integrated set of neuronal elements, (the System), which contains some number of Subsystems, defined as having a higher level of temporally-integrated causality than the whole System. Each Subsystem exists from the point-of-view of the System, in the form of meaningful content. In this paper, I review the TICL and consider the importance of EM forces as a mechanism of neural causality. Using five major characteristics of phenomenal consciousness as a standard, I compare the basic tenets of Integrated Information Theory, Global Neuronal Workspace, General Resonance Theory, Operational Architectonics, and the Temporo-spatial Theory of Consciousness with the framework of the TICL. While the literature concerned with these theories tends to focus on different lines of evidence, there are fundamental areas of agreement. In time, it may be possible for many of them to converge upon the truth. In this analysis, I conclude that a primary distinction which divides these theories is the feature of spatial and temporal nesting. This distinction does not separate along the fault line between theories explicitly concerned with EM fields and those which are not. Reconciliation is possible, at least in principle, among those theories that recognize the following: Just as the contents of consciousness are distinctions within consciousness, the neural correlates of conscious content should be distinguishable from but fall within the spatial and temporal boundaries of the full neural correlates of consciousness.